2022
DOI: 10.17306/j.afs.2022.1010
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplements in therapy to support weight reduction in obese patients [pdf]

Abstract: Obesity is a pandemic disease that poses a serious problem for the entire world population. Preventative and non-pharmacological treatments for obesity include changing eating habits and increasing physical activity. The use of certain dietary supplements also brings beneficial results in the process of reducing excess body weight. There are many options for the treatment of obesity available on the pharmaceutical market. This study aims to review the latest publications on selected dietary supplements in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…Commercial supplements rarely describe the MW of chitosan. Still, it is shown that any MW chitosan used as a food supplement reduces the absorption of fat and cholesterol [42]. Chitosan diets generally reduce plasma lipid levels and increase the excretion of fat and cholesterol in the feces [31].…”
Section: Chitosanmentioning
confidence: 99%
“…Commercial supplements rarely describe the MW of chitosan. Still, it is shown that any MW chitosan used as a food supplement reduces the absorption of fat and cholesterol [42]. Chitosan diets generally reduce plasma lipid levels and increase the excretion of fat and cholesterol in the feces [31].…”
Section: Chitosanmentioning
confidence: 99%
“…In particular, it has been observed that obese individuals have lower levels of PYY compared to normal-weight individuals. This suggests that PYY may be involved in the pathophysiology of obesity ( 169 ). The exact mechanisms through which PYY regulates body weight are still not fully understood.…”
Section: Hormone Associated With Obesitymentioning
confidence: 99%